2005
DOI: 10.1111/j.1751-1097.2005.tb01459.x
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin‐fullerene C60 Dyads with High Ability to Form Photoinduced Charge‐separated State as Novel Sensitizers for Photodynamic Therapy

Abstract: The photodynamic activities of a porphyrin‐C60 dyad (P‐C60) and its metal complex with Zn(II) (ZnP‐C60) were compared with 5‐(4‐acetamidophenyl)‐10,15,20‐tris(4‐methoxyphenyl)‐porphyrin (P), both in homogeneous medium‐bearing photooxidizable substrates and in vitro on the Hep‐2‐human‐larynx‐carcinoma cell line. This study represents the first evaluation of dyads, with a high capacity to form a photoinduced charge‐separated state, to act as agents to inactivate cells by photodynamic therapy (PDT). Absorption an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Milanesi et al 78 compared PDT with a porphyrin-C 60 dyad (P-C 60 ) and its metal complex with Zn(II) (ZnP-C 60 ) were compared with 5-(4-acetamidophenyl)-10,15,20-tris(4-methoxyphenyl)porphyrin (P), both in homogeneous medium containing photooxidizable substrates and in vitro on the Hep-2 human larynx carcinoma cell line. 1 O 2 yields (Φ Δ ) were determined using 9,10-dimethylanthracene (DMA).…”
Section: Fullerenes and Pdt Of Mammalian Cells Including Cancer Cellsmentioning
confidence: 99%
“…Milanesi et al 78 compared PDT with a porphyrin-C 60 dyad (P-C 60 ) and its metal complex with Zn(II) (ZnP-C 60 ) were compared with 5-(4-acetamidophenyl)-10,15,20-tris(4-methoxyphenyl)porphyrin (P), both in homogeneous medium containing photooxidizable substrates and in vitro on the Hep-2 human larynx carcinoma cell line. 1 O 2 yields (Φ Δ ) were determined using 9,10-dimethylanthracene (DMA).…”
Section: Fullerenes and Pdt Of Mammalian Cells Including Cancer Cellsmentioning
confidence: 99%
“…Although it has not yet been conclusively proven, it is possible that the highly reactive HO • is proportionately more cytotoxic than 1 O 2 on a molecule for molecule basis. Furthermore, it is reasonably well-accepted that type 1 photochemistry is less dependent on the surrounding oxygen concentration than is type 2 photochemistry (35,36). Fullerenes may be able to be relatively more effective in hypoxic tumors growing in such regions as the peritoneal cavity where pO2 levels are lower than in well-perfused tissues (37).…”
Section: Discussionmentioning
confidence: 99%
“…Milanesio et al compared the PDT effect of porphyrin-C60 and its metal complex with Zn(II) to the pure porphyrin (5-(4-acetamidophenyl)-10,15,20-tris(4-methoxyphenyl)-porphyrin) in Hep-2 cell line and concluded that the porphyrin-C60 complex had the greatest impact on cells. 379 …”
Section: Use Of Graphene-based Materials To Enhance Pdtmentioning
confidence: 99%
“…International Journal of Nanomedicine 2024:19 5660 porphyrin-C60 and its metal complex with Zn(II) to the pure porphyrin (5-(4-acetamidophenyl)-10,15,20-tris(4-methoxyphenyl)-porphyrin) in Hep-2 cell line and concluded that the porphyrin-C60 complex had the greatest impact on cells. 379 Miki et al reported the preparation of amphiphilic γ-cyclodextrin-fullerene complexes and Sugikawa et al described ROS generation. 375,380 With such molecules, it is also possible to prepare hybrid complexes of C60 and hydrophobic porphyrin by mixing in water in the presence of PEG.…”
Section: Dovepressmentioning
confidence: 99%